2021
DOI: 10.1186/s13229-021-00421-1
|View full text |Cite
|
Sign up to set email alerts
|

Is social camouflaging associated with anxiety and depression in autistic adults?

Abstract: Background There is inconsistent evidence for a clear pattern of association between ‘camouflaging’ (strategies used to mask and/or compensate for autism characteristics during social interactions) and mental health. Methods This study explored the relationship between self-reported camouflaging and generalised anxiety, depression, and social anxiety in a large sample of autistic adults and, for the first time, explored the moderating effect of gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
114
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 170 publications
(151 citation statements)
references
References 62 publications
11
114
0
Order By: Relevance
“…Table 2 provides an overview of participant characteristics for participants with autism diagnoses or high autistic traits. There were four sets of studies in which samples were partially or fully duplicated (Hull et al, 2019;Hull, Lai, et al, 2020;Hull, Levy, et al, 2021;Jorgenson et al, 2020;Bernardin et al, 2021;Lai et al, 2017Lai et al, , 2019Livingston, Shah, & Happé, 2019;Livingston et al, 2020). In these instances, only information from one study (the study with the largest N) was counted when calculating aggregated participant characteristics.…”
Section: Participant Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 2 provides an overview of participant characteristics for participants with autism diagnoses or high autistic traits. There were four sets of studies in which samples were partially or fully duplicated (Hull et al, 2019;Hull, Lai, et al, 2020;Hull, Levy, et al, 2021;Jorgenson et al, 2020;Bernardin et al, 2021;Lai et al, 2017Lai et al, , 2019Livingston, Shah, & Happé, 2019;Livingston et al, 2020). In these instances, only information from one study (the study with the largest N) was counted when calculating aggregated participant characteristics.…”
Section: Participant Characteristicsmentioning
confidence: 99%
“…Later studies quantifying both camouflaging and mental health constructs using validated measures have provided more consistent evidence suggesting that greater self-reported camouflaging (i.e., higher Total CAT-Q scores) is associated with increased neuroticism (Robinson et al, 2020); increased social anxiety, general anxiety, and depressive symptoms (Hull et al, 2019;Hull, Levy, et al, 2021); greater psychological distress (Beck et al, 2020); and decreased well-being (Hull et al, 2019; although see Perry et al, 2021). However, there was no evidence that the relationship between selfreported camouflaging and mental health outcomes was moderated by gender (Hull, Levy, et al, 2021).…”
Section: What Is the Relationship Between Camouflaging And Mental Health And Wellbeing Outcomes?mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to research on other stigmatised identities showing that more disclosure correlates with improved mental health (Quinn et al, 2014), both disclosure and concealment were associated with poorer mental health among autistic individuals . Literature within and outside of this review has also demonstrated associations between camouflaging behaviours and depression, anxiety, stress, and lower psychological well-being among autistic people (Beck et al, 2020;Cage et al, 2018;Cage & Troxell-Whitman, 2019;Hull et al, 2021).…”
Section: Discussionmentioning
confidence: 89%
“…Stigma and unconscious bias contribute to poor mental health outcomes for autistic people. Camouflaging, or hiding the fact that one is autistic, is associated with increased anxiety, depression, 13 and suicidality. 14 Since the rates of mental illness and suicide are considerably higher among doctors than other professions, raising awareness of this hidden minority of autistic doctors is critical.…”
Section: Future Directionsmentioning
confidence: 99%